2015
DOI: 10.1186/s13047-015-0092-7
|View full text |Cite
|
Sign up to set email alerts
|

Characterising the biophysical properties of normal and hyperkeratotic foot skin

Abstract: BackgroundPlantar foot skin exhibits unique biophysical properties that are distinct from skin on other areas of the body. This paper characterises, using non-invasive methods, the biophysical properties of foot skin in healthy and pathological states including xerosis, heel fissures, calluses and corns.MethodsNinety three people participated. Skin hydration, elasticity, collagen and elastin fibre organisation and surface texture was measured from plantar calluses, corns, fissured heel skin and xerotic heel sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…The skin characterisation devices have not been utilised within this patient group before. However, they have been utilised in published research in adults [ 21 , 27 ]. Extensive pilot work and comparison to other devices has been undertaken to establish this protocol as feasible, in addition to repeatability work at each laboratory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The skin characterisation devices have not been utilised within this patient group before. However, they have been utilised in published research in adults [ 21 , 27 ]. Extensive pilot work and comparison to other devices has been undertaken to establish this protocol as feasible, in addition to repeatability work at each laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…The participant will be seated with legs extended and plantar aspects of both feet facing the investigator, in an infant feeding chair, or in the arms of the parent/guardian. Five sites will be measured [ 21 , 27 ] (Fig. 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…This finding agrees with the results of Hoffmann, Ammon, Volkamer, Sürie, and Radko [ 27 ], who found a negative correlation between DC values and the severity of foot pad dermatitis (FPD) in broiler chickens; specifically the DC values were higher in foot pads with lower FPD scores and were lower in foot pads with higher FPD scores. Hashmi, et al [ 33 ] found lower levels of hydration in hyperkeratotic than in normal foot skin. Alanen, et al [ 34 ] reported that there was always some air between the probe and the skin due to the roughness of the skin.…”
Section: Discussionmentioning
confidence: 99%
“…These devices are widely regarded as “the gold standard” for measuring skin elasticity . However, they have several disadvantages: expensive and large for home‐use, should contact the skin surface during the measurement and expert knowledge is required to understand the results.…”
Section: Introductionmentioning
confidence: 99%